Towards sustainable cancer care: Reducing inefficiencies, improving outcomes—A policy report from the All.Can initiative. (September 2017) - Wait, Suzanne; Han, Daniel; Muthu, Vivek; Oliver, Kathy; Chrostowski, Szymon; Florindi, Francesco; de Lorenzo, Francesco; Gandouet, Benjamin; Spurrier, Gilliosa; Ryll, Bettina; Wierinck, Lieve; Szucs, Thomas; et al.
Graphical abstract: Highlights: Improving efficiency and investing in innovation should be considered in tandem, with the common thread being a focus on improving outcomes for patients. The collection and transparent reporting of patient-relevant outcomes data should be at the root of all efforts to improve efficiency. We need to take a whole-system view of efficiency, looking across the entire cancer care pathway. Recognising the potential for greater efficiency in cancer care is simple. Implementation, however, is more challenging and requires close collaboration among all stakeholders. Abstract: The past few decades have seen considerable advances in the way cancer is diagnosed and treated. Yet with the growing prevalence of cancer and ongoing pressures on limited healthcare budgets, equal access to the latest scientific advances and their affordability have become a challenge. In the face of limited resources and increasing demand, we need to find better ways of allocating the resources we have, and to focus on what can make the greatest difference to patients. This means both eliminating interventions that offer limited benefit and prioritising those that give the greatest benefit to patients and value to the wider system. Improving the efficiency of cancer care must start with a clear understanding of what outcomes we are trying to achieve for patients. We must (1) look across the entire cancer care pathway and move away from budget siloes and fragmentation in our current healthcare systems; (2) measure the impact of what we do by investing in the right data; and (3) use these data to drive a culture of continuous improvement with clear accountability mechanisms in place. Increasing efficiency, however, is not a goal in itself; it is a means to deliver what matters most to patients and what will achieve the greatest improvements in their care in a sustainable way. Achieving long-term efficiency in cancer care is a complex task, and all stakeholders have a role to play. Yet change has to start with policy-makers and those who decide on how healthcare funding is allocated today.